Integrative Holistic Learning Strategies in Early Childhood Education - Pattiruhu, Claudia Monique; Makulua, Korlina; Thalib, Najdah; Elizar, Elizar; Pandia, Betharia Sembiring (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
Integrative holistic learning is a process of giving full attention to early childhood to improve the quality and ability of children which includes providing nutritional health education services, protection, care and welfare. This study aims to determine the integrative holistic learning strategy in early childhood education. The research method used by researchers is a quantitative method with an observation model, namely conducting direct interviews with teachers. The results of this study indicate that it is important to add insight and broad knowledge about integrative holistic learning strategies in early childhood education. So that it can help solve existing problems and shortcomings regarding integrative holistic strategies in early childhood education, and can form an outstanding and quality generation. From this research it can be concluded that integrative holistic learning strategies in early childhood education are very important and necessary to help the role of a teacher and parents to improve the quality and achievement of children. The limitation in this study is that researchers only conducted research on integrative holistic learning strategies in early childhood education. Therefore, the researcher hopes that future researchers can conduct further research related to integrative holistic learning strategies in early childhood education to be further developed. Researchers also recommend that future researchers use the results of this study as a reference in conducting research on interactive holistic learning strategies in early childhood education.